Digital Storytelling as a Patient Engagement and Research Approach With First Nations Women: How the Medicine Wheel Guided Our Debwewin* Journey. (October 2021) - Rieger, Kendra L.; Bennett, Marlyn; Martin, Donna; Hack, Thomas F.; Cook, Lillian; Hornan, Bobbie
When research is conducted from a Western paradigm alone, the findings and resultant policies often ignore Indigenous peoples' health practices and fail to align with their health care priorities. There is a need for decolonized approaches within qualitative health research to collaboratively identify intersecting reasons behind troubling health inequities and to integrate Indigenous knowledge into current health care services. We engaged with First Nations women to explore to what extent digital storytelling could be a feasible, acceptable, and meaningful research method to inform culturally safe health care services. This novel approach created a culturally safe and ethical space for authentic patient engagement. Our conversations were profound and provided deep insights into First Nations women's experiences with breast cancer and guidance for our future qualitative study. We found that the digital storytelling workshop facilitated a Debwewin journey, which is an ancient Anishinabe way of knowing that connects one's heart knowledge and mind knowledge.